2019
DOI: 10.1108/cg-12-2018-0378
|View full text |Cite
|
Sign up to set email alerts
|

Do disclosure and transparency affect bank’s financial performance?

Abstract: Purpose The purpose of this paper is to examine the impact of transparency and disclosure on the financial performance of financial institutions. The emphasis is on assessing transparency and disclosure; auditing and compliance; risk management as indicators of corporate governance; and understanding how these parameters affect bank profitability, liquidity and the quality of loan portfolios. Design/methodology/approach A sample of 20 financial institutions was selected, with ten respondents from each, yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 38 publications
2
28
0
2
Order By: Relevance
“…Observa-se que na literatura já é possível encontrar evidências de que o disclosure de informações sobre gerenciamento de riscos de instituições financeiras apresenta relação positiva com: valorização das ações dos bancos (Jizi & Dixon, 2017), resultados financeiros (Oino, 2019), estabilidade (Del Gaudio et al, 2020) e governança (Nahar et al, 2020). Ademais, o nível de divulgação sobre riscos tem poder preditivo sobre a classificação de risco das instituições financeiras (Elamer et al, 2021) permitindo dirimir incertezas (Kim et al, 2019).…”
Section: Informações Sobre Gestão De Riscosunclassified
“…Observa-se que na literatura já é possível encontrar evidências de que o disclosure de informações sobre gerenciamento de riscos de instituições financeiras apresenta relação positiva com: valorização das ações dos bancos (Jizi & Dixon, 2017), resultados financeiros (Oino, 2019), estabilidade (Del Gaudio et al, 2020) e governança (Nahar et al, 2020). Ademais, o nível de divulgação sobre riscos tem poder preditivo sobre a classificação de risco das instituições financeiras (Elamer et al, 2021) permitindo dirimir incertezas (Kim et al, 2019).…”
Section: Informações Sobre Gestão De Riscosunclassified
“…Studies by Li (2008), Liao (2013), Melloni (2015), Oliveira (2010) and Siew (2013) are demonstrating similar results. Research conducted by Andriani Tisna (2016) on the banking industry during 2010-2014 shows that governance affects the company's financial performance, especially transparency (Oino, 2019). The research generated by Faradina (2016) during 2010-2014 shows that IC positively affects the company's financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study on the role governance in companies showed that one of its components, namely transparency and disclosure, is proven to have an influence on financial performance (Oino, 2019). Research conducted by Ratmono, Nugrahini and Cahyonowati (2021) also shows that GCG will make a sustainability report the better it is presented, with it the higher the company's performance because it gets support from its stakeholders.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Veracity (or issues of transparency and disclosure) of NPAs are usually assumed to be perfect, which may not be true all the time. This is another area to explore, and is not covered in the scope of the current study (Oino 2019). In the present study, it is assumed to be correct.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to varied measures of bank performance, there are myriad factors that may impact it. A few among them are widely researched: regulation (Delis et al 2011;Klomp and De Haan 2015); transparency and disclosures (Baumann and Nier 2004;Oino 2019); competition or market power (Ariss 2010;Tabak et al 2015); intellectual capital (Buallay et al 2019); autonomy (Barnabas and Mekoth 2010;Lybek 1999); and ownership issues (Grassa et al 2019;Sarkar and Sarkar 2018;Ozili and Uadiale 2017). Among the many factors that can have a significant impact on bank performance, it is believed that ownership concentration can have the most influence.…”
Section: Introductionmentioning
confidence: 99%